2012
DOI: 10.4172/2155-9872.1000133
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a High Performance Liquid Chromatography Method for Determination of Telmisartan in Rabbit Plasma and its Application to a Pharmacokinetic Study

Abstract: A simple and sensitive High-Performance Liquid Chromatography (HPLC) method with fluorescence detection for quantitation of telmisartan in rabbit plasma was developed and validated. Separation of telmisartan from plasma components was achieved on a Chromolith RP18e column (100 x 4.6 mm 5 µ). Losartan was used as an internal standard. A mobile phase consisting of 50 mM sodium phosphate buffer and acetonitrile in the volume ratio of 65:35 v/v was delivered at a flow rate of 3.5 mL/min.A simple and rapid sample p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In mice, peak plasma concentration (C max ) after one dose of 1 mg/Kg of TEL is 162 ng/mL after oral administration [7], but to date, we did not find a report for its plasma concentration when administered ad libitum to mice. Regarding methods to detect TEL, Virkar et al developed and validated an HPLC method with fluorescence detection in rabbit plasma [35]. Salama et al also reported the use of HPLC-UV in Human plasma, and was able to detect between 1-10 µg/mL of TEL [36].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, peak plasma concentration (C max ) after one dose of 1 mg/Kg of TEL is 162 ng/mL after oral administration [7], but to date, we did not find a report for its plasma concentration when administered ad libitum to mice. Regarding methods to detect TEL, Virkar et al developed and validated an HPLC method with fluorescence detection in rabbit plasma [35]. Salama et al also reported the use of HPLC-UV in Human plasma, and was able to detect between 1-10 µg/mL of TEL [36].…”
Section: Discussionmentioning
confidence: 99%
“…The method provided excellent selectivity and linearity, and has been successfully applied to pharmacokinetic study. 66 Development of a HPLC method for the determination of tedizolid in human plasma, human serum, saline and mouse plasma: A simple HPLC method was developed and validated to analyze tedizolid in human plasma, human serum, saline and CD-1 mouse plasma.…”
Section: Validated Methods For the Determination Of Gemifloxacin In Bulk Pharmaceutical Formulations And Human Serum By Rp-hplcmentioning
confidence: 99%
“…4 It is also determined spectrophotometrically 9 and with TLC. [10][11][12] Telmisartan is determined in human plasma, 13,14 urine [15][16][17][18][19] and binary tablets. 20,21 It is determined by HPLC analysis using C18 column 17,18,22 with mass sensitive detector, 23,24 fluorescence,…”
Section: Introductionmentioning
confidence: 99%